Tympanostomy tube placement in awake, unrestrained pediatric patients: A prospective, multicenter study. Issue 12 (December 2015) - Zeiders, Jacob W.; Syms, Charles A.; Mitskavich, Mary T.; Yen, David M.; Harfe, Daniel T.; Shields, Ryan D.; Lanier, Brent J.; Gould, Andrew R.; Mouzakes, Jason; Elliott, C. Layton
Abstract: Objectives: Tympanostomy tube (tube) placement is the most common pediatric otolaryngologic surgery in the United States. Most surgeries are performed in an operating-room setting under general anesthesia due to the lack of tolerable and reliable local anesthesia methods suitable for pediatric patients, and concerns regarding myringotomy procedures in a mobile child. This study evaluated the safety and efficacy of an iontophoresis system (IPS) to achieve local anesthesia in combination with a tube delivery system (TDS) for tube placement in pediatric patients in an office setting. Methods: A prospective, single-arm study was conducted at 9 otolaryngology sites in the United States. Participants included pediatric patients aged 6 months to less than 22 years requiring tube placement. Patients were prepared for the procedure using behavioral support techniques and tube placement was attempted under local anesthesia using the IPS in conjunction with the TDS. No physical restraints were allowed and no anxiolytics, analgesics, or sedatives were permitted. Safety was assessed through the occurrence of adverse events and success rates for tube placement under local anesthesia were determined. Tolerability of the procedure was evaluated using the 5-point Wong–Baker FACES Pain Rating Scale and parental satisfaction was assessed using a postoperative survey. Results: Seventy patients (127 ears) were enrolled in the study [mean (SD) age = 7.0 (3.9) years]. No serious adverse events occurred in the 70 enrolled patients. Tube placement using the TDS was successful in 96.6% (114/118) of attempted ears. A single TDS was required in 105 ears, while more than 1 device was required in 9 ears. Of the 70 patients enrolled in study, 63 (90.0%) successfully received tubes in all indicated ears during their in-office visit. The mean (SD) change in pain score from pre-anesthesia to post-surgery was +0.9 (1.8). Favorable ratings for overall satisfaction with the in-office procedure were obtained from 96.9% (63/65) of respondents. Tube retention at 2 weeks was 99.1%. As only 15 patients were enrolled who were 3 years old or younger, the ability to generalize these results to younger patients is limited. Conclusions: In this study, use of the IPS and TDS technologies enabled safe, reliable, and tolerable placement of tubes in awake, unrestrained pediatric patients.